The Atypical Short-Chain Dehydrogenases HCF173 and HCF244 Are Jointly Involved in Translational Initiation of the psbA mRNA of Arabidopsis(1)([W]) - Link, Sabine (American Society of Plant Biologists, 2012)
The related proteins D1 and D2 together build up the photosystem II reaction center. Synthesis of D1 (PsbA) is highly regulated in all photosynthetic organisms. The mechanisms and specific protein factors involved in controlled expression of the psbA gene in higher plants are highly elusive. Here, we report on the identification of a chloroplast-located protein, HCF244 (for high chlorophyll fluorescence244), which is essentially required for translational initiation of the psbA messenger RNA in Arabidopsis (Arabidopsis thaliana). The factor is highly conserved between land plants, algae, and cyanobacteria. HCF244 was identified by coexpression analysis of HCF173, which encodes a protein that is also necessary for psbA translational initiation and in addition for stabilization of this messenger RNA. Phenotypic characterization of the mutants hcf244 and hcf173 suggests that the corresponding proteins operate cooperatively during psbA translation. Immunolocalization studies detected the majority of the two proteins at the thylakoid membrane. Both HCF244 and HCF173 are members of the atypical short-chain dehydrogenase/reductase superfamily, a modified group, which has lost enzyme activity but acquires new functions in the metabolism of the cell.